Case Report: Sacral Nerve Root Pelvic Neural Retraining, With Long-Term Sustainability After the Device Explantation - Vassiliu, Panteleimon; Patoulis, Filippos; Naar, Leon; Dendias, Georgios; Arkadopoulos, Nikolaos (Frontiers in Rehabilitation Sciences, 2021)
Introduction: Sacral-Nerve-Neuromodulation (SNM) is an effective treatment increasingly used in patients with urinary (UI) and fecal incontinence (FI). The way it acts in the body at its full potential have not yet been elucidated. The authors review the literature on SNM and the way it possibly works, relating it to a case with an unusually favorable outcome. Case Presentation: A female presented with UI and FI. Operated for meningocele as a neonate. It the age of 5 bilateral Cohen ureter reimplantation performed for persistent urinary infections due to vesicourethral reflux. At the age of 13, she started complaining about UI associated with a hyper functional detrusor muscle. After a diary incontinence evaluation with a standardized questionnaire, SNM was applied at the age of 18 and was retained for 4 years. She was re-evaluated with a yearly follow-up. Results: The patient retained the positive effect of SNM even after its removal and in addition showed signs of improvement. The patient developed the sensation of fillingness of the bladder and the rectum, which she never had before the SNM implantation, sensation which she retained 29 months after (last follow-up) device removal, allowing her to control her voids. Discussion: The modern literature hypothesis that SNM contributes to the plasticity of the nerves through the stimulated area is supported by the present case, in which the SNM effect remained and led to improvements even after its removal. Device settings are presented as they may correlate with the result. This reinforces and expands the frontiers of SNM application and research.